Energy transfer in pendant perylene diimide copolymers. Issue 35 (18th August 2016) - Davis, Nathaniel J. L. K.; MacQueen, Rowan W.; Roberts, Derrick A.; Danos, Andrew; Dehn, Sabrina; Perrier, Sébastien; Schmidt, Timothy W.
Abstract : We report the synthesis and characterisation of novel copolymers comprising asymmetric perylene diimide acrylate monomers. Abstract : We report the synthesis, characterisation and polymerisation of two novel asymmetric perylene diimide acrylate monomers. The novel monomers form a sensitiser–acceptor pair capable of undergoing Förster resonance energy transfer, and were incorporated as copolymers with tert -butyl acrylate. The tert -butyl acrylate units act as spacers along the polymer chain allowing high concentrations of dye while mitigating aggregate quenching, leading to persistent fluorescence in the solid state at high concentrations of up to 0.3 M. Analysis of fluorescence kinetics showed efficient energy transfer between the optically dense sensitiser and the lower concentration acceptor luminophores within the polymer. This reduced reabsorption within the material demonstrates that the copolymer-scaffold energy transfer system has potential for use in luminescent solar concentrators.